Towards an understanding of GPs' viewpoint on diagnosing postnatal depression in general practice: a small-scale realist evaluation. (9th October 2020) - Sriranjan, Ashvanthi Nadira; Abrams, Ruth; Wong, Geoff; Park, Sophie
Abstract: Background: Less than half of postnatal depression cases are identified in routine clinical assessment. Guidelines and current literature suggest that general practitioners (GPs) may have an opportunistic role in detecting postnatal depression due to their early contact and existing rapport with many new mothers. There is limited research on the diagnostic approaches chosen by GPs in different GP−patient contexts. Our small-scale study evaluates the thought processes of seven GPs based in one practice when forming a clinical diagnosis of postnatal depression under different contexts. Methods: Seven GP participants were interviewed using case vignettes about postnatal depression, based on an adapted Johari's window framework. A realist approach to analysis was undertaken with the intention of understanding GPs' responses to different situations. Context−mechanism−outcome configurations were constructed, and a programme theory was formed to consolidate the findings. Findings: Findings suggest that diagnoses may be a clinician-led or collaborative process between GP and patient. In collaborative contexts, stigmatising views were addressed by GPs, time for self-reflection was encouraged and mothers' views were accounted for. Clinician-led diagnoses often occurred in contexts where there was a lack of acknowledgement of symptoms on behalf of the patient or where safety was a concern. The personal and clinical experience of GPs themselves, as well as effective communication channels with other primary care professionals, was significant mechanisms. Conclusion: GPs use a variety of strategies to support patient disclosure and acceptance of their condition. The complexity of GP−patient contexts may influence the clinical thought process. We address some of the gaps in existing literature by exploring postnatal depression diagnosis in primary care and provide tentative explanations to suggest what works, for whom and in what contexts.